Archeology, Conservation and Enhancement: The Role of Viability in the UK Planning System. (3rd July 2019) - Phillips, Dan
ABSTRACT: In England, since the publication of the 2012 National Planning Policy Framework, viability has taken an elevated role in the planning process with economic viability becoming an important consideration in the determination of a planning application. In this paper, the author introduces viability as a relatively new formal assessment brought into the UK planning system and explores ways in which it may impact existing provisions in place to protect the historic environment. The article highlights the complexities of adopting the Viability Assessment model and provides cases in which these assessments have been used to mitigate planning obligations in place to conserve and enhance the historic environment. In light of the current application of viability models during the planning process by developers, the author calls on the need for more research in this area as well as the need for further awareness of its use by those working to conserve and enhance the historic environment. Ultimately, the article aims to set Viability Assessment against the broader principles of sustainable development and recommends perusing the concept of a Cultural Capital Valuation for UK heritage.